(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
This paper aims to discuss the definition of men posing as women from the Islamic perspective, the banning of such acts by the Quran and Hadith and the forms of punishment meted out under the Johore Syariah Criminal Offences Enactment provision. The methodology used in this research is the study of documents such as books, articles and court related cases. The findings indicate that there is a prohibition in legislation regarding men posing as women and there are other provisions with which a person may be charged in addition to the original provision (for example the Johore Syariah Criminal Offences Enactment which should serve as a model for other states in Malaysia) so that the legal provisions cannot be challenged by other laws. With these improvements in legislation it is hoped that the noble Muslim’s morality is preserved. Keywords: men posing as woman, law, punishment